Cognitive and Language Development at Age 4–6 Years in Children HIV‐Exposed But Uninfected Compared to Those HIV‐Unexposed and to Children Living With HIV. Issue 171 (3rd July 2020) - Gruver, Rachel S.; Mall, Sumaya; Kvalsvig, Jane D.; Knox, Justin R.; Mellins, Claude A.; Desmond, Chris; Kauchali, Shuaib; Arpadi, Stephen M.; Taylor, Myra; Davidson, Leslie L.
Abstract: Perinatal HIV infection is associated with delayed neurocognitive development, but less is known about children perinatally HIV‐exposed but uninfected (CHEU). We compared cognitive and language outcomes in 4–6‐year old CHEU versus children HIV‐unexposed and uninfected (CHUU) and children living with HIV (CLHIV). We enrolled 1, 581 children (77% of the child population) in five communities in KwaZulu‐Natal, South Africa. Children completed: Grover‐Counter Scale of cognitive development, sub‐scales of the Kaufman Assessment Battery for Children, Reynell Developmental Language Scales. HIV status of children and primary caregivers was determined by repeated rapid tests or report of prior testing. We conducted a cross‐sectional multivariable linear regression on 922 dyads with complete data (257 CHEU, 627 CHUU, 38 CLHIV). On all outcome measures, CHEU and CHUU groups had comparable scores; CLHIV scored significantly lower. Emerging global progress toward the elimination of vertical HIV transmission may not only reduce mortality, but also positively impact child development.